Hierarchical Co and Nb dual-doped MoS2 nanosheets shelled micro-TiO2 hollow spheres as effective multifunctional electrocatalysts for HER, OER, and ORR. (April 2021) - Nguyen, Dinh Chuong; Luyen Doan, Thi Luu; Prabhakaran, Sampath; Tran, Duy Thanh; Kim, Do Hwan; Lee, Joong Hee; Kim, Nam Hoon
Abstract: Heteroatom doping engineering has emerged as an intriguing strategy to enhance electrocatalytic efficiency. Herein, a multiple transition metal doping approach is developed through the incorporation of both Co and Nb into hierarchical MoS2 ultrathin nanosheets directly grown on micro-TiO2 hollow spheres (Co, Nb-MoS2 /TiO2 HSs) to boost the hydrogen evolution (HER), oxygen evolution reaction (OER), and oxygen reduction reaction (ORR). The Co and Nb dual-doping effects modify the electronic structure of the host MoS2 towards maximizing the HER, OER, and ORR performance. Additionally, the unique hollow spherical structure and heterostructured synergistic effects between the TiO2 core and MoS2 shell provide effective channels for electron transfer and large surface area with abundant exposed void spaces for ion diffusion/penetration. Therefore, the Co, Nb-MoS2 /TiO2 HSs catalyst demonstrates extraordinary activity and stability with small overpotentials of 58.8 and 260.0 mV at 10 mA cm −2 for the HER and OER, respectively. When employed as both cathodic and anodic electrode in an electrolyzer, the catalyst requires an operating voltage of 1.57 V to achieve 10 mA cm −2 . The catalyst also exhibits great potential for the ORR with high onset potential of + 0.96 V and half-wave potential of +0.87 V, as well as direct four-electron transfer process. Graphical Abstract: ga1 Highlights: Novel structure of Co, Nb dual-doped MoS2 NSs on TiO2 hollow spheres was prepared. Co, Nb-MoS2/TiO2 HSs showed good activity and durability for HER, OER, and ORR. Co, Nb-MoS2/TiO2 HSs-assembled electrolyzer displayed expected performance.